Estradiol Level and Psychosocial Stress in Perimenopausal Women - Levita, Lucia L; Hadiprodjo, Hadiprodjo; Abdullah, Nusratuddin; Pelupessy, Nugraha U (Indonesian Socety of Obstetrics and Gynecology, 2019)
Objective : To determine the relationship between estradiol levels and psychosocial stress in the perimenopausal women. Methods : Sixty perimenopausal included in a cross-sectional study from July to December 2016. Blood samples obtained from the women to measure the estradiol and the cortisol levels. Stress level measured with visual. Data presented as the mean and standard deviation (mean±SD) with p-value <.05 was considered statistically significant.  Results : There was no significant difference between the estradiol levels and the stress level (p=0.27) during perimenopause period. The estradiol levels were higher compared with the cortisol levels. The non parametrik correlations analysis show the estradiol levels were not correlated with the cortisol levels (p=0.352). However, the cortisol levels were correlated with the stress levels (p<0.05). Conclusion : Estradiol does not cause psychosocial stress during perimenopause period in our study population Keywords : Estradiol, psychosocial stress, perimenopause